Can immunohistochemistry quantification of Cathepsin-D be useful in the differential diagnosis between vital and post-mortem wounds in humans?. (July 2014) - Montisci, Massimo; Corradin, Matteo; Giacomelli, Luciano; Viel, Guido; Cecchetto, Giovanni; Ferrara, Santo Davide
Markers of skin wound vitality and the research methodology used for their determination are still matters of debate in forensic pathology. Cathepsin-D, a lysosomal enzyme, is the most expressed cathepsin in human skin, and although it seems to have the necessary requirements to be utilized as a vitality marker, past research has provided no definitive and clear response on its potential usefulness. Immunohistochemistry with monoclonal antibodies and image analysis has been employed to detect and quantify the expression of Cathepsin-D in human skin wounds. We analyzed skin fragments obtained from 20 living individuals (group A) and 20 persons deceased from natural causes (group B). For each case, five skin fragments were withdrawn at 0′, 5′, 10′, 30′, and 90′ after abdominal incision. Once the samples were formalin-fixed and paraffin-embedded, we analyzed the expression of Cathepsin-D through the quantification of the immunohistochemistry signal by image analysis. Immunoreactivity was displayed in Pixels of positive area measured by image analysis and converted in micrometer squares. The average levels of Cathepsin-D were higher in group B than in group A, except in three cases which showed a lower expression, with a statistically significant difference of Cathepsin-D expression between the two groups ( p  < 0.0001). Group B showed unvaried levels among the progressive samples and group A revealed an increasing predominant trend at 30′. Due to the high levels of expression of Cathepsin-D found in the post-mortem injuries, our study definitively excludes any usefulness of immunohistochemistry quantification of this enzyme in the differentiation between vital and post-mortem injuries.